POLÍTICA E PRÁTICA DO MATERIAL DIDÁTICO KANHGÁG NA ESCOLA: UM ESTUDO NA TERRA INDÍGENA RIO DAS COBRAS NO PARANÁ - FERNANDES, DANUSA KORIG BERNARDO (2023)
It presents research data on the policies and practices of Kanhgág didactic material at school, as a study carried out in the Rio das Cobras Indigenous Land in the State of Paraná. Research developed in the Graduate Program in Education of the State University of the Midwest (Unicentro), in line with educational policies and is linked to the work of the Laboratory of Rural and Indigenous Education and the Research Group Field, Social Movements and Rural Education. The problem involves the hegemonic presence of Portuguese textbooks in school; the lack of specific didactic material in the Kaingang language; scarce bilingual Kanhgág-Portuguese materials; rare research in the area; lack of ordering of what exists produced for/with Kanhgág in school libraries; the need to train an indigenous teacher to make use of the teaching materials present in the school. Do you question which Kanhgág or bilingual school teaching materials make up the collection of school libraries in Rio das Cobras and what strategies of use are possible? Analyzes the school teaching materials present in schools; catalogs the collection of school textbooks; verifies the possibilities of use of didactic materials in pedagogical practices. It opts for qualitative research, from the investigation of reality itself, indigenous subject, articulates personal biography, Kanhgág biography and being a researcher. It carries out bibliographic study; analysis of documents of the five Kanhgág schools in the Rio das Cobras territory in Nova Laranjeiras-PR, of a universe of 39 indigenous schools in the state of Paraná; and performs a circle of dialogue on the uses of didactic material for bilingual teaching with a group of six indigenous teachers. He considers that the history of the Rio das Cobras Indigenous Land is fundamental in strengthening the current school situation. It highlights the significant presence of indigenous teachers with Higher Education in schools and this as a potential for a policy of production of bilingual didactic material for schools. It concludes that the work of cataloging the documents in school libraries makes evident the presence and absence of material for bilingual teaching and the realization of pedagogical practices in the intercultural school, differentiated as provided by the law. It shows that the teacher training programs developed in the territory have produced great theoretical and practical contributions. There is the challenge of following the analysis of the documents and producing new research.